Evaluating the Likely Adoption of a University Mobile App at WBS in South Africa - Savvides, Michael George (My University, 2017)
ABSTRACT This research paper set out to determine what the likely adoption would be of a new university mobile App amongst the current Wits Business School students in Johannesburg. The increased usage of mobile technology amongst students sets the expectation of wanting information to be available at their fingertips at any time, and anywhere. The supremacy of mobile technology has a significant influence on a student’s life as it creates effective lines of communication and engagement, where students increasingly want to conduct university activities on their smartphone devices via a mobile App. The aim of this paper was to identify the factors that have an influence on a student’s decision to adopt a new university mobile App, as well as to investigate the relative impact each of the independent variables has on the student’s intention to adopt the App. Using a Technology Acceptance Model (TAM) as the theoretical framework, it was discovered, after analysing the questionnaires, that the factors and key drivers that would need to be tackled for successful adoption are Trust; Perceived Value; and Social Influence. The results showed that 83.75% of students would adopt a new university App. Based on this, it gave rise to and justified the creation of a business case in the final chapter of the report. Using the primary research and secondary research data from literature, and addressing the key drivers in the design and development of the proposed new App, a financially viable business model resulted. This validated the formation of the business case, where the Wits Business School are effectively asked to invest a specific amount of capital to get the new mobile App developed and introduced into the Business School by the start of the 2018 academic year. Keywords: University mobile App; TAM; WBS Students; Business Case
M.B.A. Thesis
Keywords: Consumer behavior, Application software, Mobile computing -- South Africa.